THE METHOD OF MEASURING AIRWAY RESISTANCE IN PRESCHOOL CHILDREN, BASED ON THE TECHNIQUE BRIEFLY INTERRUPTING THE FLOW: BRONCHODILATORS TEST'S PRACTICE - N.V. Malyuzhinskaya; A.V. Razvalyaeva; M.V. Garina; A.V. Shatalin; V.A. Gorbunov (Union of pediatricians of Russia, 2011)
Objective: To evaluate the prospects of a new noninvasive technique for measuring airflow obstruction in pediatrics. Materials and methods: The spirograph SuperSpiro with module MicroRint. Indicators of airflow obstruction (FEV1, PEF) and airway resistance (Rint) before and after inhalation of 200 micrograms salbutamol (test with bronchodilator) were measured in 36 children of 5-6 years old with asthma. Calculated the growth/fall in the second attempt on the outcome of each method, then the data series for each method were compared with each other. Results: FEV growth averaged 14,5%, an increase of PEF - 17,5% by the end. Fall Rint index averaged 0,25 kPa/l/s. Under positive-sum test according to the ERF (30 patients out of 36) Rint drop occurred in all cases, and an average of 0,28 kPa/l/s with. Correlation (Rint and FEV r = -0,93, Rint and PEF r = -0,96) between the indices is very high. Conclusion: The technique Rint is an alternative to the classical spirometry in young children.Key words: children, allergic diseases, bronchial asthma, airway resistance, test with bronchodilator.